Peningkatan Kualitas Ampas Kelapa melalui Fermentasi dengan Suplemen Organik Cair sebagai Pakan Ayam Kampung - Nurtania Sudarmi; Aswandi; Bersemina Mofu (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2020)
Agricultural people are responsible for providing food, such as meat, eggs and milk. In providing meat, especially chicken, the cost of feed becomes an obstacle for breeders. The local wisdom of plants in Papua is an opportunity to create quality local feed. Utilization of dregs can be used as an alternative ration. The low nutrient content contained in coconut dregs requires a touch of technology to optimize coconut dregs into quality feed. The fermentation process can be a solution to these problems. The experiment used a completely randomized design (CRD) with three treatments and 6 replications. R0 = 100% Basal Feed (BF); R1 = BF 80% + Fermented Coconut Dregs 20%; R2 = BF 60% + Fermented Coconut Dregs 40%. The implementation stages consisted of (1) coconut dregs fermentation stage and (2) In-Vivo test on native chickens with the observed variables: feed consumption, body weight gain and feed conversion. The results showed that fermented coconut dregs could be given as starter phase native chicken feed without disturbing the metabolic process. The average provision of coconut dregs as native chicken feed with variable feed consumption, average daily gain (ADG), and FCR had no significant effect (P> 0.05). This means that the addition of fermented coconut dregs up to 40% has not had a significant effect on ration consumption, ADG, and FCR, so further studies are needed. Keywords: Chicken, Coconut Dregs, Consumption, ADG, FCR